HIV disclosure in the social networks of adolescents with HIV in Cape Town, South Africa - Mulawa, Marta I.; Hung, Frances; Phillips, Nicole J.; Austin, Mark F.; Barfield, Richard; Lee, Hui-Jie; Zar, Heather J.; Stein, Dan J.; Hoare, Jacqueline (Frontiers in Reproductive Health, 2025)
BackgroundLittle is known about HIV status disclosure within the social networks of adolescents with perinatally-acquired HIV (APHIV) in sub-Saharan Africa, where HIV prevalence is high and stigma surrounding HIV is pervasive. This study employed egocentric network analysis to characterize HIV disclosure in the social networks of APHIV in Cape Town South Africa. Associations between HIV disclosure and characteristics of APHIV (egos), their relationship to network members (alters), and features of the social network, including ego's network size and alter's centrality within the network, were also examined.MethodsNetwork data were collected from 58 APHIV (mean age 14.3 years; 52% female) using a customized touchscreen-based assessment, providing data on 349 ego-alter relationships. Associations with HIV disclosure within the ego-alter pairs were evaluated by adjusted odds ratios (AOR) from multivariable logistic regression with generalized estimating equations, clustering by ego.ResultsAmong all ego-alter pairs identified, 36.4% (127/349) were disclosed to by egos. Odds of disclosure did not differ based on the ego's gender or viral suppression. Odds of disclosure were significantly higher when alters were presumed by the ego to have HIV [AOR 6.26; 95% confidence interval (CI): 2.36–16.58, p < 0.001], were more trusted by the ego (AOR 2.84; 95% CI: 1.14–7.06, p = 0.03), or were older than the ego (1-year difference AOR 1.04; 95% CI: 1.02–1.07, p < 0.001). Increasing alter's centrality by 0.01 was associated with an increased odds of disclosure (AOR 1.02; 95% CI: 1.002–1.03, p = 0.03), though overall network size was not associated with increased odds of disclosure. The effect of the ego's emotional support network size on disclosure, however, depended on the type of ego-alter relationship.ConclusionsHIV status disclosure was low in the social networks of APHIV. Our study found that disclosure was not influenced by network size, gender, or viral suppression but rather by factors related to interpersonal trust and shared experience, such as perceived HIV status of alters, network-level centrality and emotional support network size. The study further highlights the benefits and future potential of using social network data collection and analysis methods to better understand HIV disclosure among adolescents.